Penguatan Pemahaman Tentang Fungsi dan Nilai Rumah Adat Lopo bagi Masyarakat Adat Meto di Desa Mnelalete Kabupaten Timor Tengah Selatan untuk Memperkuat Pembelajaran Sejarah - Malkisedek Taneo; Stevridan Yantus Neolaka (Universitas Nusa Cendana, 2022)
The problem with this service focuses on the degradation of the function and cultural values of the Lopo traditional house for the Meto indigenous people in Mnelalete Village, TTS District. This has an impact on the community because the Lopo traditional house which is a self-identity and collective social capital of the community is almost lost. As a result, the Lopo traditional house, which has the power of social capital, does not provide value and function, or meaning for the empowerment of the Meto people. Therefore, several solutions can be formulated through the IbM (Science and Technology for the Community) program including Helping to provide reinforcement and understanding, preserving the Lopo traditional house, realizing values, and strengthening functions and values. The methods used in this activity are lectures, brainstorming, and Focus Group Discussion (FGD)